Perception of Mosque administrators and the Mosque goers on Mosque libraries in the state of Selangor, Malaysia - Nur Leyni Nilam Putri Junurham (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2019)
A mosque plays an important role as a centre for spreading Islam. This has been proven since the time of Prophet Muhammad (PBUH). Mosque libraries are vital in opening up readership opportunities to the society. However, only limited empirical studies looked into the establishment of Mosque libraries, particularly on the perceptions of mosque administrators and mosque goers. This study attempted to explore the current situation of mosque libraries in the state of Selangor. In this regard, the perceptions of mosque administrators and mosque goers towards mosque libraries were examined. The research objectives were; RO1: To identify the current state of mosque libraries in selected districts of Selangor, RO2: To examine the perceptions of mosque administrators of mosque libraries, and RO3: To examine the perceptions of mosque goers of mosque libraries. Ten mosques from the Districts in Selangor were selected for the study. Qualitative and quantitative methods were employed, and data were gathered through interviews and questionnaires. Ten mosque administrators were selected and two hundred eighty (280) mosque goers were involved as respondents. In order to ensure the validity of data collected and analysed, the triangulation technique was employed. The findings show that, most mosques have reading corners and few libraries. Three out of ten selected mosques have a specific room for libraries. Moreover, the collections were acquired through donation and all were about religion. Besides, staffs manning the library were not qualified, and they spent most of their time on mosque activities instead of mosque library activities. Only one mosque has an annual budget for acquiring library materials and other library purposes. The perceptions of mosque administrators and mosque goers were positive about mosque libraries. The study revealed that mosque libraries were important in certain activities including reference, relaxation, and socializing. The existence and development of mosque libraries depended on certain factors as revealed from the findings such as sufficient staffs, reading habits, understanding with regards to mosque libraries' roles and functions, location, sufficient space provision, and high Key Performance Indicator (KPI) in relation to JAIS assessment. This study revealed that mosque libraries were not given the necessary assistance to perform their roles and functions to support leisure reading, learning and information seeking in the mosques. Recommendations based on these findings were that the annual budget for mosques could be reviewed, governing authorities to provide policy and advice on mosque libraries, administrators be trained to manage and promote mosque libraries. Generally, the mosque administrators and mosque goers perceived mosque libraries as important. Hence, this study contributed a guideline for improvement of mosque libraries in Selangor as there were few publications conducted under this study.